Synthesis of Some Thiazolidinone and Azetidinone Compounds and Their Antimicrobial Activity - B. Desai, Sunil; Desai, P.B.; Desai, K.R. (Asian Journal of Chemistry, 2010)
In the present report we have synthesized various thiazolidinones and azetidinines and screened them for their biological activity.